Tobacco Use in Schizophrenia: A Literature Review - Nishikant Thorat; Soham Kulkarni (BJPsych Open)
Aims: Schizophrenia is a mental illness with chronic course and varied outcomes, characterized by positive, negative, affective and cognitive symptoms along with aggression. Tobacco use is notably more prevalent in individuals with schizophrenia, often accompanied by severe dependence, compared with the general population. This literature review aims to explore the neurobiological mechanisms underlying tobacco use in schizophrenia, as well as potential treatment options and their associated benefits to the individual.